Strategic integration of marketing and supply chain functions for superior customer experience: Insights from logistics startups under Saudi Vision 2030 - Dhafer Alahmari; Abdelrehim Awad (PLoS ONE, 2025)
In the rapidly transforming logistics sector of Saudi Arabia the integration of marketing and supply chain functions is becoming ever more essential to deliver outstanding customer experiences. Though there has been ample theoretical debate, empirical proof of such integration in startup settings—especially in emerging economies—remains limited. This study explores the impact of five dimensions of integration—marketing strategies, supply chain competencies, digital integration, customer-oriented practices, and service performance—on customer experience in Saudi Arabia logistics tech startups. A survey of 384 customers of ten digital logistics platforms was conducted using a questionnaire. Through correlation and multiple regression analysis (using VIF for testing multicollinearity), the study confirms the strong positive effects of all five constructs, with the most dominant contribution of service performance (β = 0.276, p < 0.001). The model explains 53.5% variance in customer experience. Findings highlight the contribution of operational consistency and digital alignment to trust, satisfaction, and loyalty. The research fills a gap in the literature by presenting evidence from an underrepresented setting and offers insight in line with Vision 2030 agendas.